Penetapan Status Daerah Khusus Ibu Kota Negara dalam Mewujudkan Kesejahteraan Ummat - Rosidin, Utang (Jurnal Studi Agama dan Masyarakat, 2018)
This paper is aimed at investigating the status determination of State Capital City and its influence in establishing people welfare. The method used in this study is descriptive analysis method by explaining a whole general description and systematic phenomena occurred. Determination of territory becoming state capital city as a special territorial unit in accordance with Article 18B of the 1945 Constitution of the Republic of Indonesia is regulated by historical factor, regional needs factor, and regional atmosphere factor. Then, it is regulated through specific laws established by the government on the basis of philosophical, juridical, and sociological aspects. The regional government of